TRANSLATION OF FIGURATIVE SENSES IN BIANGKELADI INTO ENGLISH IN THE MASTERMIND - Taopan, Talita Kum; Sudipa, I Nengah; Gde Sosiowati, I Gusti Ayu (JOURNAL OF LANGUAGE AND TRANSLATION STUDIES, 2016)
ABSTRACTSome textual materials are occasionally using figurative language. Figurative language is used in any form of communication, such as in daily conversation, articles in newspaper, advertisements, novels, poems, etc. The aim of this study is to analyze the translation procedures applied in translating figurative senses taken from a short story entitled Biangkeladi and translated into The Mastermind. Based on the analysis, there are two common procedures applied; there are transposition and modulation. By considering the figurative senses, the translator should have more attention to choose the lexicon used in TL and the lexicon used is appropriate to convey the meaning in TL ABSTRAKBeberapa teks ada kalanya menggunakan gaya bahasa majas, yang digunakan dalam berbagai ragam komunikasi, seperti dalam percakapan sehari- hari, dalam tulisan artikel, Koran, majalah, novel, puisi dan lainnya. Tujuan dari penelitian ini adalah menganalisis prosedur penerjemahan yang digunakan dalam menerjemahkan tulisan bergaya bahasa majas yang diambil dari sebuah cerita pendek berjudul Biangkeladi dalam bahasa Indonesia sebagai bahasa sumber dan diterjemahkan ke dalam bahasa Inggris sebagai bahasa target. Dari hasil penelitian, terdapat dua prosedur penerjemahan yang dipakai, yaitu Transposition dan Modulation. Dengan memperhatikan penggunaan gaya bahasa majas, seorang penerjemah akan memilih kata yang tepat untuk digunakan pada bahasa target dan kata yang digunakan dapat mengimplementasikan arti dari bahasa sumber